Pengembangan Multimedia Interaktif Melalui Smart Application Creator pada Mata Pelajaran IPA Kelas V SD Negeri Gunungpring 1 Muntilan - Safitri, Nindya Retia (Prosiding University Research Colloquium, 2021)
This study aims to: (1) produce interactive multimedia products through Smart Application Creator in the 5th-grade science lesson of Gunungpring 1 state elementary school, Muntilan. (2) determine the effectiveness of the developed products. The type of research that already done conducted is Research and Development through 10 stapes. The participants in the preliminary field testing involved 5 students. The participants in the main field testing involved 8 students and operational field testing involved 18 students, all test subjects were 5th-grade students of Gunungpring 1 state elementary school, Muntilan. The instrument to collect the data were an interview guide, product evaluation sheets, test, and questionnaire. The data were analyzed using qualitative and quantitative methods. The feasibility is also supported by the results of the material expert's assessment, score of 4.6 in the “very feasible” category. The results of the media expert's assessment score of 4.5 in the “very feasible” category. The results of the assessment in the initial field trial score of 4.8 in the “very feasible” category. The results of the assessment in the main field trial score of 4.9 in the “very feasible” category. The results of the assessment on the operational field trials score of 5.0 in the “very feasible” category. This interactive multimedia has a very good effectiveness based on the results of the paired sample t-test with a significance level of less than 5% and is shown through an increase learning outcomes by 27% with an average score of the pre-test being 65,3 and post-test 89,3. The results show that the developed interactive multimedia has very feasible and effectiveness.